Usutu virus-induced meningoencephalitis in immunocompetent mice is characterized by the recruitment of mononuclear cells and a proinflammatory T helper 1 response - Rocha, Rebeca Froes; Coimbra, Laís D.; Fontoura, Marina A.; Ribeiro, Guilherme; Sotorilli, Giuliana Eboli; Gomes, Giovanni F.; Borin, Alexandre; Felipe, Jaqueline; Slowikowski, Emily; Greison, Wilias Silva Santos; Cunha, Thiago M.; Marques, Pedro Elias; et al. (Journal of virology, 2025)
Mosquito-borne viruses, including USUV, are maintained in nature through complex cycles involving arthropod vectors and vertebrate hosts. A comprehensive understanding of USUV biology and host-pathogen interactions is crucial for developing effective treatments, which necessitates reliable experimental models (G. J. Sips, J. Wilschut, and J. M. Smit, Rev Med Virol 22:69–87, 2012, https://doi.org/10.1002/rmv.712 ; T. C. Pierson and M. S. Diamond, Nat Microbiol 5:796–812, 2020, https://doi.org/10.1038/s41564-020-0714-0 ). The establishment of a USUV infection model in immunocompetent adult mice brings new perspectives on the inflammatory component of viral encephalitis, which is difficult to study in mice lacking antiviral interferon responses. Moreover, USUV is an emerging viral disease lacking therapeutic and preventive measures. The interplay of USUV pathogenesis and the host’s immune response indicates that lymphocytes and monocytes participate in USUV infection in this model and could be explored in search of treatments targeting immunopathogenic processes triggered by infection.